LEVELS OF IRRIGATION ON GROWING Amaranthus cruentus L. DEPENDING ON THE EVAPORATION OF MINI-TANK EVAPORIMETER - de Melo, Mara Rúbia Mendes [UNESP]; Lambert, E Ricardo Alexandre (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
Research on amaranth is still incipient in Brazil, however the culture has promising prospects, and it is important to conduct more studies to verify which physiological processes, morphological and phenological changes of the plant change as a function of irrigation. The research objectives were to determine the real water requirement of amaranth, through different irrigation depths and to study the effect on the yield and characteristics of amaranth. The treatments evaluated were 90%; 120%; 150%; 180%; 210% evaporation. Daily evaporation was observed by a mini-tank evaporimeter. The parameters measured and evaluated were the number of leaves, stem diameter and height, root length, shoot fresh mass, root fresh mass, shoot dry mass and root dry mass. Length, width, fresh and dry weight of the inflorescence and commercial production per plant and weight of a thousand seeds. Deficit as well as excessive water depths promoted the lowest observed averages in most of the evaluated parameters; the 180% blade was the one that best favors the final development; and the blade that provided the highest productivity was 210%. It was concluded that amaranth has a high water requirement.
NÍVEIS DE IRRIGAÇÃO NO CULTIVO DE Amaranthus cruentus L. EM FUNÇÃO DA EVAPORAÇÃO DE MINI-TANQUE EVAPORÍMETRO
Keywords: amaranth; irrigation depth; morphological; production